A methods engineering study on ALTITUDE '88 International, Incorporated - Mendoza, Lloren; Ogardo, Ethel; Otara, Lea. (Diliman, Quezon City College of Engineering, 1999)
A method study was done on the production system of the Altitude '88 International Inc., a garment manufacturing industry based in #17 West Avenue, Quezon City. The problems of the existing system of the company were analyzed using the streamline analysis, a technique for problem identification. It was then found out that plant layout problems, poor working condition and unavailable machines and equipment were the company's main problem. These problems were subjected to further discussions and analysis. The plant and layout analysis concentrated on the narrowness of passages and doors, which causes slow and difficult transport of materials. This also discussed the idleness of the second floor area of the plant. The plant was found to have poor working conditions. It has hot working environment. Furthermore, protective gears are not provided for the workers. The chairs used by sewers in the sewing section are not comfortable. The unavailability of important machines and equipment causes much ineffective time and effort. Manual spreading of fabric requires more time and manpower as compared to that required when an electric spreader is used. Likewise, manual transport of materials causes much inconvenience, considering the heavy weight of the materials usually transported and the narrowness of the path these are passed through. Storage racks for the cut and sorted fabrics is also not available. These force the use of the floor as the temporary storage, which causes these fabrics damage and accumulation of dirt. Some minor problems were also given attention, such as the readability of forms in the standards and procedures and the undefined job assignment. Recommendations were proposed based on the problem analysis. Plant layout recommendations involve the proposed layout of the conveyor's path for the use of the second floor area. For the first floor, change in the location of the fire exit and the acquisition of a storage rack, in the cutting section are proposed. For improved working condition, a drinking fountain is to be provided in those poor ventilated sections of the factory. Protective gears should be made available and detachable foam or cushion must be provided for those sewers not comfortable with the wooden chairs presently used. The availability of scrap containers is also proposed to avoid maintenance problems. The acquisition of electric spreader and mobile transport equipment is recommended to improve those manual processes, mentioned. A storage rack should be provided in the cutting section to avoid fabric damage and accumulation of dirt. Implementation strategies are presented at the end of the study to support these recommendations.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Altitude '88 International Incorporated; Clothing trade; Systems analysis